PENERAPAN METODE ROLE PLAYING UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA PADA MATERI DRAMA - Pinteniate, Ananda; Alfi Syahrin; Muhammad Darwis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the improvement of speaking skills among eighth-grade students of SMP Negeri 23 Takengon in drama material through the application of the Role Playing method. Speaking skill is a crucial communicative competence in Indonesian language learning, and Role Playing is expected to facilitate the development of this skill by engaging students in portraying characters, which can boost confidence and fluency in speaking. This study employed a quantitative pre-experimental method with a one-group pretest-posttest design. The sample consisted of 27 eighth-grade students of class VIII.2 at SMP Negeri 23 Takengon, selected through purposive sampling. Data were collected through observation, an oral speaking skill test administered before (pretest) and after (posttest) treatment, and documentation. Data were analyzed using the Kolmogorov-Smirnov normality test, the paired sample t-test, and N-Gain calculation. The results show a significant increase in students' average score, from 38.78 at pretest to 87.63 at posttest, with an N-Gain score of 0.86 (high category). The paired sample t-test produced a significance value of 0.000 (p < 0.05), indicating that H1 is accepted and H0 is rejected. These findings confirm that the Role Playing method has a significant effect on improving students' speaking skills in drama material, particularly by reducing psychological barriers such as shyness and building students' confidence through direct role enactment. The study implies the need for teachers to further develop innovative and contextual Role Playing-based learning models to optimize students' speaking competence.